Multi-level Governance – New Applications of the Concept - Lackowska, Marta (Journal of Public Governance, 2009)
The article presents new empirical applications of the concept of multi-level governance (MLG), elaborated and used mainly in studies of the European integration. The metropolitan discourse and the theory on MLG in the European Union have many features in common. The author stresses that MLG gives an interesting perspective in metropolitan studies, especially in the case of loose institutional metropolitan structures, which complies with the main assumption of multi-level governance, i.e. interactions between many autonomous yet interconnected actors.